Medication Adherence, Work Performance and Self-Esteem among Psychiatric Patients Attending Psychosocial Rehabilitation Services at Bangalore, India - Gandhi, Sailaxmi (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: Work benefits mental health in innumerable ways. Vocational rehabilitation can enhance self-esteem. Medication adherence can improve work performance and thereby the individuals’ self-esteem. AIM: To test the hypothesis that there would be a significant correlation between medication adherence, work performance and self-esteem. SETTING AND DESIGN: A quantitative, descriptive correlational research design was adopted to invite patients attending psychiatric rehabilitation services to participate in the research. MATERIAL AND METHODS: Data was collected from a convenience sample of 60 subjects using the ‘Medication Adherence Rating scale’, ‘Griffiths work behaviour scale’ and the ‘Rosenberg's Self-esteem scale’. STATISTICAL ANALYSIS USED: Analysis was done using spss18 with descriptive statistics, Pearsons correlation coefficient and multiple regression analysis. RESULTS: There were 36 males and 24 females who participated in this study. The subjects had good mean medication adherence of 8.4 ± 1.5 with median of 9.00, high mean self-esteem of 17.65 ± 2.97 with median of 18.0 and good mean work performance of 88.62 ± 22.56 with median of 93.0. Although weak and not significant, there was a positive correlation (r = 0.22, P = 0.103) between medication adherence and work performance; positive correlation between (r = 0.25, P = 0.067) medication adherence and self–esteem; positive correlation between (r = 0.136, P = 0.299) work performance and self-esteem. Multiple regression analysis showed no significant predictors for medication adherence, work performance and self-esteem among patients with psychiatric illness. CONCLUSIONS: Medication monitoring and strengthening of work habit can improve self-esteem thereby, strengthening hope of recovery from illness.